Penerapan Sistem Informasi Geografis dalam Pemetaan Sebaran Kasus Gizi Buruk - Aris Sudianto; Muhammad Wasil; Mahpuz Mahpuz (Infotek: Jurnal Informatika dan Teknologi, 2021)
Malnutrition or Malnutrition is a general term that refers to a medical condition caused by an improper or inadequate diet. The main cause of malnutrition is the lack of children in getting enough energy and protein foods. This is with the economic level of the community. In addition, for parents' knowledge about the importance of nutrition for child development. In East Lombok, cases of malnutrition always appear every year, but recently in 2019, cases of malnutrition were rediscovered which ironically was always known too late. This is because the location of malnutrition sufferers is not reachable or is not known by the district government, this is what makes the handling of malnutrition cases in East Lombok district late, which often results in deaths of infants and children. For this reason, in this study the researcher raised the theme of how to map the distribution of the location of well-known cases of malnutrition in East Lombok district. The purpose of this study was to help the East Lombok fogapen government to see the location of people with malnutrition. The research method used is to directly record the coordinates of the location of people with bad nutrition. with this application, it can help the government in alerting the location of cases of malnutrition in East Lombok district